Assessing additional benefit in noninferiority trials - Kieser, Meinhard; Stucke, Kathrin (Biometrical journal, 2016)
A method for simultaneously assessing noninferiority with respect to efficacy and superiority with respect to another endpoint in two-arm noninferiority trials is presented. The procedure controls both the average type I error rate for the intersection-union test problem and the frequentist type I error rate for the noninferiority test by α while allowing an increased level for the superiority test. For normally distributed outcomes, two methods are presented to deal with the uncertainty about the correlation between the endpoints which defines the adjusted levels. The operating characteristics of these procedures are investigated. Furthermore, the sample size required when applying the proposed method is compared with that of alternative procedures. Application of the method in the situation of binary endpoints and mixed normal and binary endpoints, respectively, is sketched. An illustrative example is provided demonstrating implementation of the proposed approach in a clinical trial.
First published: 30 June 2014
Gesehen am 11.05.2020